Natural H2 in Kansas: Deep or shallow origin?. (8th May 2017) - Guélard, J.; Beaumont, V.; Rouchon, V.; Guyot, F.; Pillot, D.; Jézéquel, D.; Ader, M.; Newell, K. D.; Deville, E.
Abstract: A geochemical study of gas coming from three wells in northeastern Kansas supplements previous studies from the 1980s and points to a persistent regional phenomenon of H2 production. In 2008, a new well showed, just after drilling, a free gas phase with more than 80 mole % of H2, followed by water production associated with gas. This gas is mainly composed of N2, He, H2, and occasionally CH4, with changing proportions through time. A drastic decrease in H2 at the well was observed since the aquifer is produced, along with occasional recharges in H2 evidenced notably in the early phases of gas sampling. We demonstrate that this evolution of gas composition is closely associated to the well completion story. Accordingly, two distinct origins of H2 are proposed: (1) deep crustal H2 : water reduction associated to iron oxidation in the Precambrian basement; (2) reactions occurring in the tubing, primarily attributed to high contents of reduced iron and/or dissolved organic carbon (DOC = 4.1 mg L −1 ) in the water. The low δD values averaging −760‰ are attributed to a low temperature process, possibly a re‐equilibration with water. Furthermore, the suggested origins are supported by the observed gas associations: (a) deep crustal H2 with radiogenic gases ( 4 He and 40 Ar) and metamorphic N2 (δ 15 N averaging +2.5‰); (b) surficial H2 with methane produced in the sedimentary aquifer and the tubing by methanogenic organisms. Key Points: Reappraisal of a persistent regional H2 production in intracontinental settings, Kansas, USA H2 occurrences in intracratonic context: a crustal origin and a surficial origin Geochemical properties of reduced gas combination in intracontinental settings